ИЗУЧЕНИЕ ВНЕАУДИТОРНЫХ РАБОТ ПО КАРАКАЛПАКСКОЙ ЛИТЕРАТУРЕ В АКАДЕМИЧЕСКИХ ЛИЦЕЯХ - Алламбергенов, К.; Юсупов, К.А. (SCIENCE and SOCIETY, 2018)
The article is devoted to the study of extracurricular lessons in Karakalpak literature for the students of academic lyceums. On the basis of the opinions of the famous methodologists, the authors of the article distinguish such kinds of extracurricular work as: a literary conference, party, work in the club, exhibition corner, publication of journals and wall newspapers, literary trip and others.
Keywords: the process of the lesson; literature; specialist in literature; poetry; poem; character; creative work; style; method; writing; genre; language; training; literary conference; activity of the club; extra classes; exhibition corner; together with that brought out literary magazines and wall newspapers; literary trip